Given:
![a=-\dfrac{3}{4}](https://tex.z-dn.net/?f=a%3D-%5Cdfrac%7B3%7D%7B4%7D)
![b=\dfrac{4}{5}](https://tex.z-dn.net/?f=b%3D%5Cdfrac%7B4%7D%7B5%7D)
To verify:
![a\div b\neq b\div a](https://tex.z-dn.net/?f=a%5Cdiv%20b%5Cneq%20b%5Cdiv%20a)
Solution:
We have,
![a=-\dfrac{3}{4}](https://tex.z-dn.net/?f=a%3D-%5Cdfrac%7B3%7D%7B4%7D)
![b=\dfrac{4}{5}](https://tex.z-dn.net/?f=b%3D%5Cdfrac%7B4%7D%7B5%7D)
Now,
![a\div b=\dfrac{a}{b}](https://tex.z-dn.net/?f=a%5Cdiv%20b%3D%5Cdfrac%7Ba%7D%7Bb%7D)
![a\div b=\dfrac{-\dfrac{3}{4}}{\dfrac{4}{5}}](https://tex.z-dn.net/?f=a%5Cdiv%20b%3D%5Cdfrac%7B-%5Cdfrac%7B3%7D%7B4%7D%7D%7B%5Cdfrac%7B4%7D%7B5%7D%7D)
![a\div b=-\dfrac{3}{4}\times \dfrac{5}{4}](https://tex.z-dn.net/?f=a%5Cdiv%20b%3D-%5Cdfrac%7B3%7D%7B4%7D%5Ctimes%20%5Cdfrac%7B5%7D%7B4%7D)
...(i)
And,
![b\div a=\dfrac{b}{a}](https://tex.z-dn.net/?f=b%5Cdiv%20a%3D%5Cdfrac%7Bb%7D%7Ba%7D)
![b\div a=\dfrac{\dfrac{4}{5}}{-\dfrac{3}{4}}](https://tex.z-dn.net/?f=b%5Cdiv%20a%3D%5Cdfrac%7B%5Cdfrac%7B4%7D%7B5%7D%7D%7B-%5Cdfrac%7B3%7D%7B4%7D%7D)
![b\div a=\dfrac{4}{5}\times (-\dfrac{4}{3})](https://tex.z-dn.net/?f=b%5Cdiv%20a%3D%5Cdfrac%7B4%7D%7B5%7D%5Ctimes%20%28-%5Cdfrac%7B4%7D%7B3%7D%29)
...(ii)
From (i) and (ii), it is clear that
![a\div b\neq b\div a](https://tex.z-dn.net/?f=a%5Cdiv%20b%5Cneq%20b%5Cdiv%20a)
Hence verified.
Answer:
the answer would be b my friend
Step-by-step explanation:
Answer:
C is correct answer
Step-by-step explanation:
x² + 3x -4
x²+4x-1x -4
x(x+4) -1( x+4)
(x-1)(x+4)
Answer:
7 units
Step-by-step explanation: